MSc IT: MSc IT project management system / Noor Farah Eliana Abdullah - Abdullah, Noor Farah Eliana (2019)
The project management system is a system for managing, controlling, monitoring, retrieving the final year projects and one of the features in Project Management System is Information Repository. The problem statement that have been identified are students lack of knowledge about IT Project and coordinators keep the IT Project records in manually. This project developed the MSc IT Project Management System for MSc IT Student and Coordinator to manage IT Project submission and coordination respectively. The objectives of this project are to identify the user requirement in developing the web-based MSc IT project management system for Master IT students and coordinators, to design the web-based MSc IT project management system based on user requirement and to develop web-based application MSc IT project management system using Information Architecture Methodology. Information Architecture Methodology approach is used for the development of MSc IT Project Management System which focus on four phases namely Research, Strategy, Design and Implementation. PHP and PhpMyAdmin has been used as main software to develop MSc IT project management system. The MSc IT Project Management System enable student to search and retrieve for IT Project related information, provide submission checking list as well as view and download past IT Project Abstract. In addition, system provides communication platform between coordinators and students including notification on important dates and reminders of submission. This system also enable coordinator to manage IT Project in a systematically such as adding new student data, viewing student submission as well as uploading and downloading files. Based on user testing, students have agreed that the system is useful in terms of its usability and findability. Meanwhile, coordinators have recommend for the system to be used as an IT Repository for IT Project. The future recommendation for this system is to extend the functionalities for examiners and supervisors.